Application of Bacillus tequilensis for the control of gray mold caused by Botrytis cinerea in blueberry and mechanisms of action: inducing phenylpropanoid pathway metabolism - Du, Qianjie; Li, Raoyong; Liu, Li; Chen, Lin; Tang, Junrong; Deng, Jia; Wang, Fang (Frontiers in Microbiology, 2024)
Botrytis cinerea a blueberry grey mould, is one of the main diseases affecting postharvest storage, causing significant losses. To better control the postharvest gray mould of blueberry, the effects of KXF 6501 fermentation solution (YY) and KXF6501 cell-free supernatant (SQ) on the induction of disease resistance in blueberry fruits were studied using biochemical and transcriptomic analyses. The results showed that YY and SQ controlled the conidial germination and mycelial growth of B. cinerea in vitro. After 3 d of culture, the lesion diameter and incidence of gray mould in blueberry fruits inoculated with YY and SQ were significantly smaller than those in the control group. Transcription spectrum analysis of blueberry peel tissue showed that the YY- and SQ-induced phenylpropane metabolic pathways had more differentially expressed genes (DEGs) than other biological pathways. In addition, biochemical analyses showed that YY and SQ treatments effectively enhanced the activity of enzymes related to the phenylpropane pathway (phenylalanine ammonia-lyase [PAL], cinnamate 4-hydroxylase [C4H], 4-coumarate CoA ligase [4CL], and polyphenol oxidase [PPO]) and stimulated the synthesis of lignin, total phenols, and flavonoids. Compared with the control, the YY and SQ treatments reduced the weight loss rate and better maintained the appearance and nutritional quality of the blueberry fruits. Thus, it can be concluded that Bacillus tequilensis KXF6501 is potentially useful as a suitable bio-control agent in harvested blueberries.